Instrument validation to determine the relationship between social media acceptance and cuti-cuti 1 Malaysia facebook user engagement / Khairulhimi A Manap, Muhamad Shamsul Ibrahim and Nan Zakiah Megat Ibrahim - A Manap, Khairulhimi; Ibrahim, Muhamad Shamsul; Megat Ibrahim, Nan Zakiah (Universiti Teknologi MARA, 2020)
The organisation is struggling to find a way to use social media effectively as it creates much interest and could offer so many things to users. Thus, many organisations have changed to use social media to keep up with the current trend and to stay relevant. The online community tends to be influenced by social networking tool and its interactive ability. Social media content for tourism for example can become an alternative source of information for users to plan their holiday to the preferred destinations. Facebook also acts as main user source of information because they could get direct and most recent feedback from the Facebook community. Thus, this study is conducted to determine the relevance variable related to Facebook user involvement to search for information. Relevance variables are identified using factor analysis for its validity and reliability. The analysis omitted 31 items from 61 in total after the validation and reliability test. Thus, the study found that only subjective norms, perceived behaviour control, Facebook user experience, Facebook user response, and Facebook user engagement are the remaining variables that are relevant in this research context. In addition, correlation test results indicate that there is a relationship between the subjective norms and perceived behaviour control with Facebook user experience, the Facebook user experience and Facebook user response with Facebook user engagement.